Stable isotopic reconstruction of dietary changes across Late Antiquity and the Middle Ages in Tuscany. (October 2020) - Riccomi, Giulia; Minozzi, Simona; Zech, Jana; Cantini, Federico; Giuffra, Valentina; Roberts, Patrick
Highlights: Bone collagen δ 13 C and tooth enamel δ 13 C indicate a C3 resources based-diet during Late Antiquity. Bone collagen δ 13 C and tooth enamel δ 13 C indicate a mixed C3 and C4 resources based-diet during the Middle Ages. Human bone collagen δ15N indicates input of terrestrial and marine/aquatic protein. Faunal bone collagen δ15N indicates discrepancy in pig herding practice between Late Antiquity and the Middle Ages. Abstract: The transition from Late Antiquity to the Medieval period is considered one of the greatest periods of social, political, and economic upheaval in Europe, and has left its mark on the historical consciousness of people in this part of the world. Nevertheless, there remains considerable debate as to the degree to which the diets and economic status of different sections of society were impacted by this transition, with these so-called 'Dark Ages' often being uniformly considered as static and impoverished, particularly for populations along the Mediterranean rim. Such questions are especially important in central Italy, with its position at the former core of the Roman Empire leaving it most vulnerable to the major social and political shifts of the first millennium AD. However, direct insights into the diets of individuals in this region, across this key period, have been scarce, particularly in diachronic perspective. Here, we apply stable carbon (δ 13 C) and nitrogen (δ 15 N) analysis to bone collagen (n = 76), and stable carbon (δ 13 C) and oxygen (δ 18 O) isotope analysis to tooth enamel (n = 34), to human, and associated faunal, individuals dated to Late Antiquity (3rd–5th centuries AD) and the Medieval period (mid 6th–mid 13th centuries AD) in Tuscany. δ 13 C measurements of both tooth enamel bioapatite and bone collagen suggest that a predominantly C3 diet during Late Antiquity was gradually supplemented by increased C4 consumption during the Medieval period. We interpret this as a shift from an agricultural focus on wheat following the Roman agrarian tradition towards the inclusion of millet as a reliable fallback food. We argue that this was part of a growing local and regional resilience amongst communities in the Medieval period, with more diverse agricultural systems and cultural preferences following a transition from the Roman classical civilization toward a Germanic tradition whose economy was based on the diverse cultivation of "minor crops" and close integration of pastoral husbandry livestock.